Removal of Methyl Orange Using Hybrid Spherical Silica Adsorbents - Boushara, R.S.H. (2022)
This study investigated the potential adsorption behaviour of methyl orange onto a hybrid spherical silica adsorbent. Removal of dye has been a problem worldwide, and the study of removing dye through the adsorption method is quite limited. This study aims to synthesize and characterize spherical silica (SSi) adsorbent and evaluate its adsorption capacity (Qe). The spherical silica adsorbent (SSi) was prepared using oil-in-water (o/w) emulsion polymerization modification where Tetraethyl Orthosilicate (TEOS) acts as the silica precursor. The physicochemical properties of SiNs were characterized using Fourier transform infrared (FTIR), field emission scanning (FESEM), nitrogen adsorption/desorption analysis (NAD), and transmission electron microscopy (TEM). The batch adsorption study for the methyl orange removal parameters such as pH (2-10 ) and agitation time (0-180 minutes). The experimental adsorption data were further evaluated using several adsorption kinetic models, namely pseudo-first-order, pseudo-second-order and Elovich kinetic models. The diffusion kinetics model includes the Weber-Morris plot, Fickâs Law equation and Boyd plot. The result shows that the spherical silica (SSi) adsorbent at pH 2 has the highest adsorption capacity amongst other adsorbents towards methyl orange, which is 45.05 mg/g. Furthermore, the equilibrium time for methyl orange adsorption onto SSi was 120 min. The data fitted into a pseudo-second-order kinetic model indicating chemical adsorption, limited by film diffusion. Â© 2022 Trans Tech Publications Ltd, Switzerland.